SAHABAT PUBER "A Great Way for Kids to Learn About Puberty" - Nurfitriani, Yuzita; Anugerah Hadi Sulistyo, Angger; Ardianti, Ikha; Yuli A, Niken; Rizky K, Fitria; Sulistya Rahayu, Rining (Jurnal Humanis ( Jurnal Pengabdian Masyarakat ISTeK ICsada Bojonegoro), 2026)
Puberty is a crucial transitional phase marked by biological, psychological, and social changes, yet it is often considered taboo to discuss, especially in rural areas. This situation results in a low understanding of the changes experienced by elementary and junior high school children, as well as limited communication between children, parents, and the school environment. This Community Service Program aims to improve children's knowledge, attitudes, and readiness to face puberty through a door-to-door personal education approach supported by child-friendly digital media. The activity, titled SAHABAT PUBER (Great Facilities for Children to Learn About Puberty Based on Digital), was carried out in Pagerwesi Village, Trucuk District, Bojonegoro Regency, targeting 30 children aged 9–15 years. The methods used included individual and small group education, the use of animated videos, interactive infographics, simple quizzes, and active parental involvement in the educational process. Evaluation was carried out through pre- and post-tests to measure knowledge gains. The results of the activity showed a significant increase in children's understanding of puberty, changes in attitudes to be more positive and confident, and increased openness of communication between children and parents. This program has proven effective as a contextual, inclusive, and sustainable model of reproductive health education, and has the potential to be replicated in other regions with similar characteristics.